Curricular Development in a Post-Secondary School Commercial English Language Program for Adults in Ukraine - Tarnopolsky, Oleg; Storozhuk, Svitlana (International Journal of Publication and Social Studies, 2017)
The article discusses curricular development in a program designed for post-secondary school commercial teaching of English to adults. The teaching is organized in English language courses that function outside college/university language training programs. The curriculum structure and its components are discussed; the foundations of curricular development are analyzed, as well as the goals of teaching set in the program and the methods of teaching and learning used in it. The analysis of goal, content, organization, and other aspects of such curricula is conducted on the basis of theoretical assumptions and practical experience. That experience is of 25-year-long duration and based on the work of the Foreign Language Center (FLC) functioning on the premises and under the aegis of Alfred Nobel University in Dnipro, Ukraine. The spectrum of the courses offered is considered in the paper and it is demonstrated that it consists of: a) General English courses of different levels; b) courses preparing students for taking international (Cambridge) examinations in English; c) courses of English for Specific (Professional) Purposes (ESP). The communicative-analytic approach underlying all the courses in the developed program is discussed and the most important features of that approach are summarized. The ways of using learners’ needs analysis for determining goals, selecting the content, and determining what methods of teaching/learning to use in every course in the program are outlined, as well as the means of organizing separate courses while ensuring their diversity, autonomy, and integrity in the framework of the entire language program.